Functionalizable Antifouling Coatings as Tunable Platforms for the Stress-Driven Manipulation of Living Cell Machinery - Víšová, Ivana; Smolková, Barbora; Uzhytchak, Mariia; Vrabcová, Markéta; Chafai, Djamel Eddine; Houska, Milan; Pastucha, Matěj; Skládal, Petr; Farka, Zdeněk; Dejneka, Alexandr; Vaisocherová-Lísalová, Hana (Biomolecules, 2020)
Cells are continuously sensing their microenvironment and subsequently respond to different physicochemical cues by the activation or inhibition of different signaling pathways. To study a very complex cellular response, it is necessary to diminish background environmental influences and highlight the particular event. However, surface-driven nonspecific interactions of the abundant biomolecules from the environment influence the targeted cell response significantly. Yes-associated protein (YAP) translocation may serve as a marker of human hepatocellular carcinoma (Huh7) cell responses to the extracellular matrix and surface-mediated stresses. Here, we propose a platform of tunable functionable antifouling poly(carboxybetain) (pCB)-based brushes to achieve a molecularly clean background for studying arginine, glycine, and aspartic acid (RGD)-induced YAP-connected mechanotransduction. Using two different sets of RGD-functionalized zwitterionic antifouling coatings with varying compositions of the antifouling layer, a clear correlation of YAP distribution with RGD functionalization concentrations was observed. On the other hand, commonly used surface passivation by the oligo(ethylene glycol)-based self-assembled monolayer (SAM) shows no potential to induce dependency of the YAP distribution on RGD concentrations. The results indicate that the antifouling background is a crucial component of surface-based cellular response studies, and pCB-based zwitterionic antifouling brush architectures may serve as a potential next-generation easily functionable surface platform for the monitoring and quantification of cellular processes.
Keywords: buněčný převod mechanických signálů; Cell Line, Tumor; protoonkogenní proteiny c-yes; Biofouling; mechanický stres; Acrylamides; extracelulární matrix; Oligopeptides; Stress, Mechanical; Proto-Oncogene Proteins c-yes; biokompatibilní potahované materiály; Coated Materials, Biocompatible; lidé; Humans; Mechanotransduction, Cellular; Extracellular Matrix; akrylamidy; bioznečištění; nádorové buněčné linie; oligopeptidy